SKEMA DAN AL-TAKYÎF AL-FIQH (TINJAUAN FIKIH) PEMBELIAN ANUITAS DALAM PROGRAM PENSIUN - Sanrego, Yulizar D (al-'adalah, 2015)
Abstract: The Scheme and the Legal Assessment (al-Takyîf al-Fiqh) on the Purchase of Annuity in Retirement Program. The business scheme in a contract of annuity is actually an effort to provide additional monthly income to its participants. In the program, each participant works together to put aside a certain amount of their pension funds to assist other participants in fulfilling their monthly needs. Such a contract, viewed from the perspective of legal assessment (al-takyîf al-fiqh}, is actually a grant based on the Ruqbâ contract or a combination between ruqbâ and business contracts. In Ruqbâ contract, the mauhîb (the grant) given by the wâhib (the grantor) is owned by mauhîb lah (recipient) throughout his life and after his death. In the business contract, on the other hand, the contract may use a fee as in mutual benefit contract (murâbaha). Both types of the mentioned above contracts are allowed in Islam.Abstrak: Skema dan Tinjauan Fikih (al-Takyîf al-Fiqh) terhadap Pembelian Anuitas dalam Program Pensiun. Skema bisnis yang berlaku dalam kontrak anuitas sesungguhnya merupakan upaya untuk memberikan tambahan pendapatan bulanan kepada para peserta. Dalam program ini masing-masing peserta bertabarru’ dalam menggunakan dana pensiunnya (baik secara keseluruhan maupun periodik) untuk membantu peserta lain dalam menutup keperluan bulanannya. Akad yang demikian, berdasarkan analisis al-takyîf al-fiqh, sebenarnya merupakan aqad hibah secara ruqbâ atau penggabungan antara Ruqbâ dan Aqad bisnis. Dalam ruqbâ, mauhîb yang diberikan oleh wahîb menjadi milik yang diberi (mauhîb lah) sepanjang hidupnya dan setelah dia meninggal. Sementara untuk skema bisnis, akad yang boleh digunakan adalah melalui murâbahah. Hukum dari kedua macam akad di atas dalam Islam adalah boleh.